Surgical Outcomes of Biventricular Repair for Hypoplastic Left Ventricle With Congenital Mitral Valve Stenosis. Issue 1 (January 2019) - Shimada, Masatoshi; Hoashi, Takaya; Nakata, Tomohiro; Ozawa, Hideto; Kurosaki, Kenichi; Kitano, Masataka; Ichikawa, Hajime
Objective: Surgical outcomes of biventricular repair for hearts with hypoplastic left ventricle with congenital mitral valve stenosis are described. Serial changes of left ventricular geometry and clinical features after biventricular repair were reviewed. Methods: Eight patients with hypoplastic left ventricle and congenital mitral valve stenosis who underwent first surgical intervention for biventricular circulation in neonatal or infantile period between 2001 and 2014 comprise the study population. Serial change in left ventricular end-diastolic diameter, left ventricular mass index, and relative wall thickness after biventricular repair were evaluated by two-dimensional echocardiography. Results: The median Z -scores of left ventricular end-diastolic diameter and mitral valve diameter before the first surgical intervention were −3.0 (range, −4.8 to −2.0) and −1.0 (−2.9 to 2.1), respectively. Mitral valves were surgically treated in five patients; they were replaced in two and repaired in three patients. Left ventricular end-diastolic diameter Z -score at five years after biventricular repair was 0.1 (−3.0 to 1.0), which was significantly larger than before first surgical intervention ( P = .005). Left ventricular mass index, on the other hand, did not change, but relative wall thickness significantly decreased ( P = .009). Postoperative catheter study showed pulmonary hypertension with high left ventricular end-diastolic pressure in more than half of survivors. Conclusions: Left ventricle increased in size after the biventricular repair with appropriate mitral valve procedures before progression of pulmonary hypertension. Left ventricular mass, however, did not accompany the increase. Some patients may have suffered from mild, but certain restrictive left ventricular physiology and subsequent pulmonary hypertension as the result of abnormal remodeling process of the myocardium.